Increased phospholipase A2 and decreased lysophospholipase activity in the small intestinal mucosa after ischaemia and revascularisation. Issue 11 (November 1987) - Otamiri, T; Franzén, L; Lindmark, D; Tagesson, C
Abstract : The influence of ischaemia and revascularisation on lipid peroxidation and phospholipid metabolism in the rat small intestinal mucosa was investigated. Two hours of total ischaemia followed by five minutes of revascularisation caused not only accumulation of malondialdehyde in the mucosa, but also increased activity of phospholipase A2, decreased activity of lysophospholipase, and increased ratio between lysophosphatidylcholine and phosphatidylcholine. Pretreatment with the phospholipase A2 inhibitor, quinacrine, prevented the increases in mucosal phospholipase A2 activity and lysophosphatidylcholine/phosphatidylcholine ratio after ischaemia and morphological examinations revealed that the mucosa was then also protected against ischaemic injury. These findings point to the possibility that activation of phospholipase A2 and accumulation of lysophosphoglycerides could be involved in mediating the mucosal injury caused by small intestinal ischaemia.